2018
DOI: 10.1007/s12599-018-0566-9
|View full text |Cite
|
Sign up to set email alerts
|

Towards Digital Transformation in Fashion Retailing: A Design-Oriented IS Research Study of Automated Checkout Systems

Abstract: Automated checkout systems promise greater sales due to an improved customer experience and cost savings because less store personnel is needed. The present design-oriented IS research study is concerned with an automated checkout solution in fashion retail stores. The implementation of such a cyberphysical system in established retail environments is challenging as architectural constraints, well-established customer processes, and customer expectations regarding privacy and convenience impose limits on syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Looking at the underlying technologies, we can identify which technologies are particularly relevant to create digital innovation value. For instance, technologies such as analytics and business intelligence [30, p. 8], augmented reality [31,32], cloud computing [33], CRM systems [19], digital control systems [34], digital platforms [30,35], digital prototyping technologies [36], project management systems [37], RFID [38], social media [39] and 3D printing [2] are some common technological foundations for digital innovation value. We uncover that digital innovation succeeds effectively in organizations when an orchestrated integration of technology in the work system and a collective consideration of the social and technical systems within an organization take place [40,41].…”
Section: Extant Research On Digital Innovation Valuementioning
confidence: 99%
“…Looking at the underlying technologies, we can identify which technologies are particularly relevant to create digital innovation value. For instance, technologies such as analytics and business intelligence [30, p. 8], augmented reality [31,32], cloud computing [33], CRM systems [19], digital control systems [34], digital platforms [30,35], digital prototyping technologies [36], project management systems [37], RFID [38], social media [39] and 3D printing [2] are some common technological foundations for digital innovation value. We uncover that digital innovation succeeds effectively in organizations when an orchestrated integration of technology in the work system and a collective consideration of the social and technical systems within an organization take place [40,41].…”
Section: Extant Research On Digital Innovation Valuementioning
confidence: 99%
“…Static tags occurred when the tags were located within the configured read range, whereas moved tags are tags that were moved through the reader gate. However, several previous retail store domain studies have shown that certain moved tags (e.g., tag movement close to the gate) were considered as false positives [23,24]. Hauser et al (2015) investigated classification models to detect false-positive RFID readings in retail stores to help prevent shop theft [23].…”
Section: False Positive Detectionmentioning
confidence: 99%
“…RSS based attributes were extracted as features for the considered classification models: DT, LR, random forest (RF), artificial neural network (ANN), and SVM. Another study revealed that integrating machine learning models with RFID could enable automated checkout systems, particularly for fashion retailing [24].…”
Section: False Positive Detectionmentioning
confidence: 99%
See 2 more Smart Citations